A Convenient Mechanism for the Free Radical Scavenging Activity of Resveratrol - Mohammed A. Hussein (International Journal of Phytomedicine, 2011)
Resveratrol(3,5,4’-trihydroxy-trans-stilbene) is a stilbenoid, a type of natural phenol, and a phytoalexin produced naturally by several plants when under attack by pathogens such as bacteria or fungi was evaluated for possible antioxidant and free radical scavenging activities. Different antioxidant tests were employed, namely, reducing power, chelating activity on Fe2+, free radical-scavenging, total antioxidant, superoxide radical scavenging, hydrogen peroxide scavenging and hydroxyl radical scavenging activities. In addition, the results were compared with natural and synthetic antioxidants, such as α- tocopherol, ascorbic acid, butylated hydroxytoluene(BHT), butylated hydroxyanisole (BHA) and trolox. Resveratrol exhibited a strong reducing power, chelating activity on Fe2+, free radical-scavenging, hydrogen peroxide scavenging and hydroxyl radical scavenging activities. Antioxidant activity of resveratrol increased with increased concentrations.Total antioxidant activity of resveratrol and both standards decreased in the order of α-tocopherol > resveratrol > trolox > BHA > BHT. This study showed that resveratrol exhibited antioxidant activity in all tests and could be considered as a source of natural antioxidants.